1997
DOI: 10.1038/sj.onc.1200849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ALK, a receptor tyrosine kinase expressed specifically in the nervous system

Abstract: The 2;5 chromosomal translocation is frequently associated with anaplastic large cell lymphomas (ALCLs). The translocation creates a fusion gene consisting of the alk (anaplastic lymphoma kinase) gene and the nucelophosmin (npm) gene: the 3' half of alk derived from chromosome 2 is fused to the 5' portion of npm from chromosome 5. A recent study shows that the product of the npm-alk fusion gene is oncogenic. To help understand how the npm-alk oncogene transform cells, it is important to investigate the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
535
0
10

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(577 citation statements)
references
References 17 publications
18
535
0
10
Order By: Relevance
“…Nucleophosmin allows dimerization of the fusion protein, causing constitutive activation of ALK kinase and downstream activation of phospholipase C-g, PI3K, STATs and pp60c-src (Allouche, 2007). The native full-length ALK receptor is mainly expressed in discrete regions of the developing central and peripheral nervous system (Iwahara et al, 1997). Mourali et al (2006) forced ALK expression in cells of lymphoid and neuronal origin to investigate wild-type ALK functions.…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…Nucleophosmin allows dimerization of the fusion protein, causing constitutive activation of ALK kinase and downstream activation of phospholipase C-g, PI3K, STATs and pp60c-src (Allouche, 2007). The native full-length ALK receptor is mainly expressed in discrete regions of the developing central and peripheral nervous system (Iwahara et al, 1997). Mourali et al (2006) forced ALK expression in cells of lymphoid and neuronal origin to investigate wild-type ALK functions.…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…ALK is functionally important in embryonic development [3] and in determination of cell survival and cell fate [4]. However, ALK was originally discovered when it was found that the chimeric N-terminal nucleophosmin (NPM) domain/cytoplasmic (catalytic) ALK domain fusion protein (NPM-ALK) is the oncoprotein underlying the pathogenesis of anaplastic large cell lymphomas (ALCL) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies identified several other ALK kinase fusion proteins that support oncogenesis (Hernandez et al, 1999;Colleoni et al, 2000;Lawrence et al, 2000;Ma et al, 2000;Touriol et al, 2000;Trinei et al, 2000). Full-length ALK was initially described as an orphan receptor tyrosine kinase that shows restricted tissue distribution and is regulated during organ development (Iwahara et al, 1997;Morris et al, 1997). Several studies show expression of full-length ALK protein in cultured fibroblasts and endothelial cells as well as cell lines derived from epithelial cancers such as pancreatic and breast carcinoma (Stoica et al, 2001 and the neuroectoderm, that is, melanoma (Dirks et al, 2002), neuroblastoma Stoica et al, 2002) glioblastoma and non-Hodgkin's lymphoma (Delsol et al, 1997), reviewed by Pulford et al (2004).…”
Section: Introductionmentioning
confidence: 99%